Hydroxyapatite nanoparticles as vectors for gene delivery. (May 2012) - Tram Do, Thi Ngoc; Lee, Wing-Hin; Loo, Ching-Yee; Zavgorodniy, Alexander V; Rohanizadeh, Ramin
The long-recognized promise of gene therapy to treat a broad range of currently incurable diseases remains largely unfulfilled, hindered by lack of a safe and efficient delivery vehicle. Hydroxyapatite nanoparticles are deemed a feasible candidate and possess many characteristics desired of an ideal gene vector. Current fabrication techniques can readily synthesize hydroxyapatite particles in the nanometer range; however, these particles suffer from extensive aggregation and heterogeneity, mainly in size, shape and surface charge, which render them inappropriate for gene-therapy application. There is thus a pertinent need to develop a method capable of fabricating homogenous and monodispersed hydroxyapatite nanoparticles in a rapid, efficient and cost-effective manner that can be easily upscaled. Cell transfection is impeded by several physical and biological barriers, with the vector's properties highly determinant of its ability to overcome these barriers. Fine-tuning hydroxyapatite nanoparticles' morphological and physicochemical properties, achievable through precise regulation of the reaction environment, can enhance transfection efficiencies of particles, in turn, generating safe and effective gene vectors.